The use of the imperfect tense in European Portuguese and in European Spanish - Azevedo, Bárbara (2021)
This work has as main objective to analyze the use of the Imperfect past tense in two Romance languages, European Portuguese and European Spanish, in order to verify if their uses, in certain contexts, are equivalent or distinct. The analysis is based on data collected from two language repositories, one Portuguese (CETEMPublic) and one Spanish (CREA), as well as in Portuguese and Spanish online newspapers. The study focuses on conditional constructions in order to verify the extent to which the two languages converge or not as to the use of the Imperfect in these constructions. After analyzing the data, it was observed that there are some differences between the two languages in these constructions, based on the respective classes with which the Imperfect tense is combined.